Median and ulnar nerve conduction determinations in the Erb's point--axilla segment in normal subjects. - Ginzburg, M (1978)
Twenty-one median and 22 ulnar nerves were tested in 12 patients for motor nerve conduction velocity (MNCV) and motor nerve conduction time (MNCT) in the segments from Erb's point (N) to axilla (A) bilaterally. It was found that on this segment for both nerves, MNCV values equal to or smaller than 51 m/s or conduction times equal to or longer than 4 ms are to be considered abnormal. For comparative studies and for checking the normality of the tested nerves in their entire length, the more distally located segments in the same nerve were also tested. For diagnostic purposes, the differences between right and left MNCV or MNCT values determined in the same person on N-A segments of homologous nerves were analysed. Motor nerve conduction velocity or MNCT determinations on the N-A nerve segment are expected to replace MNCV determinations on the longer N-AE (AE=100 mm above elbow) nerve segment, which is now in use, for diagnosis of the thoracic outlet syndrome.